ACR–ARS Practice Parameter for the Performance of Total Body Irradiation. (13th May 2023) - Reilly, Michael; Dandapani, Savita V.; Kumar, Kiran A.; Constine, Louis; Fogh, Shannon E.; Roberts, Kenneth B.; Small, William; Schechter, Naomi R.
Abstract : Objectives: This practice parameter was revised collaboratively by the American College of Radiology (ACR) and the American Radium Society (ARS). This practice parameter provides updated reference literature regarding both clinical-based conventional total body irradiation and evolving volumetric modulated total body irradiation. Methods: This practice parameter was developed according to the process described under the heading The Process for Developing ACR Practice Parameters and Technical Standards on the ACR website (https://www.acr.org/Clinical-Resources/Practice-Parameters-and-Technical-Standards ) by the Committee on Practice Parameters—Radiation Oncology of the ACR Commission on Radiation Oncology in collaboration with the ARS Results: This practice parameter provides a comprehensive update to the reference literature regarding conventional total body irradiation and modulated total body irradiation. Dependence on dose rate remains an active area of ongoing investigation in both the conventional setting (where instantaneous dose rate can be varied) and in more modern rotational techniques, in which average dose rate is the relevant variable. The role of imaging during patient setup and the role of inhomogeneity corrections due to computer-based treatment planning systems are included as evolving areas of clinical interest notably surrounding the overall dose inhomogeneity. There is increasing emphasis on the importance of evaluating mean lung dose as it relates to toxicity during high-dose total body irradiation regimens. Conclusions: This practice parameter can be used as an effective tool in designing and evaluating a total body irradiation program that successfully incorporates the close interaction and coordination among the radiation oncologists, medical physicists, dosimetrists, nurses, and radiation therapists.